PREVALENCE OF ENURESIS IN SAMPLE OF IRAQI CHILDREN (Iraqi Journal of Medical Sciences, 2016)
Background:Enuresis, which is frequently diagnosed amongst school age children, is an important psychosocial problem for both parents and children.Objective:In the present study we aimed to determine the prevalence and associated risk factors of enuresis in sample of Iraqi children and to identify common methods for its management.Methods: Across sectional epidemiological study was performed among primary school age children living in Tikrit and Beji cities during the period from the October 2008 to the June 2009. A self-administered questionnaire was prepared for this study and distributed to the parents of 1.150 school age children whom aged 6-12 years.Results:Of the 1.150 questionnaires distributed, 1000 (87%) were completed. The overall prevalence of nocturnal and diurnal enuresis were 22% (n = 220) and 1.9% (n =25) respectively. Although male gender, low age, history of enuresis among parents, low educational level of the parents, deep sleep, increased number of siblings, increased numbers of people sleeping in the child's room, history of enuresis among siblings, poor school performance and history of recurrent urinary tract infections (UTI) were significantly associated with enuresis, but not with the severe enuresis. The percentage of children with enuresis seen by physician for treatment was 17.2%. The most preferred treatment option for enuresis was medications (59.5%), whereas alarm treatment was the least preferred (2.4%).Conclusion:The results with enuresis prevalence and associated risk factors were comparable to other epidemiological studies from various countries, but it is higher in our country. Furthermore we demonstrated that families in the Tikrit do not pay sufficient attention to enuresis and most of enuretic children do not receive professional treatment.Key Words:Enuresis, family characteristics, prevalence
Keywords: Enuresis; family characteristics; prevalence